(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
The paper presents theoretical and practical aspects of the impact of arts on tourist experiences. The paper will analyse both theoretical and practical aspects of experience marketing of art’s events on tourist experiences. In empirical research, the paper will present results about the segmentation of target groups of tourists who choose a tourist destination on the basis of arts events, as well as their satisfaction with arts events, exhibitions, concerts, theatres events, literary events at the time happened in the chosen destination. Results of research about tourist’s satisfaction would be important for further research on the development of a tourist destination as a brand. Social media, blog, post have an impact on the development of tourist experiences, based on art experiences. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.